2018
DOI: 10.1007/s10661-018-6702-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of ultraviolet–visible spectrophotometry associated with artificial neural networks as an alternative for determining the water quality index

Abstract: The water quality index (WQI) is an important tool for water resource management and planning. However, it has major disadvantages: the generation of chemical waste, is costly, and time-consuming. In order to overcome these drawbacks, we propose to simplify this index determination by replacing traditional analytical methods with ultraviolet-visible (UV-Vis) spectrophotometry associated with artificial neural network (ANN). A total of 100 water samples were collected from two rivers located in Assis, SP, Brazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
(29 reference statements)
0
8
0
1
Order By: Relevance
“…Many studies indicated that machine learning has potential for the analysis of single or multi-wavelength spectral data [ 10 , 20 , 21 , 22 , 23 ]. For instance, using UV absorbance spectrometry in the 250–300-nm region, Kim et al [ 24 ] used a multiple linear regression model to detect organic compounds in water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies indicated that machine learning has potential for the analysis of single or multi-wavelength spectral data [ 10 , 20 , 21 , 22 , 23 ]. For instance, using UV absorbance spectrometry in the 250–300-nm region, Kim et al [ 24 ] used a multiple linear regression model to detect organic compounds in water.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the techniques they investigated for this mapping exercise included: (i) support vector machines (SVMs), (ii) linear discriminant analysis, (iii) generalised discriminant analysis (GerDA), (iv) random forest, and (v) neural networks. Similarly, using multi-wavelength absorbance spectrometry with a feed-forward neural network, Alves et al [ 20 ] attempted to determine a river water quality index. In contrast, Chen et al [ 22 ] assessed near-infrared (NIR) spectra using the least squares support vector machine (LSSVM) to develop a method for the quantitative determination of COD.…”
Section: Introductionmentioning
confidence: 99%
“…RMSE, MAPE and R2 are often used as a criterion to estimate network performance by comparing the error and measured data obtained from conjoint neural network studies [34]. RMSE and MAPE are calculated according to Equation 1-2.…”
Section: Organic Matter Estimation With Annmentioning
confidence: 99%
“…However, machine learning has a good nonlinear approximation ability, and the application of machine learning in water quality monitoring provides a new idea to improve the accuracy of water quality monitoring. Alves simplified the input variables of the feed forward neural network through principal component analysis, thus accurately inverting the water quality index (WQI) [12]. Gogu proved that there is a good potential in using a neural network to invert the salt content of river water through experiments [13].…”
Section: Introductionmentioning
confidence: 99%